TO THE ISSUE OF CERTAINTY OF THE CONCEPT OF «HUMAN»: PHILOSOPHICAL AND LEGAL ASPECTS - Сherevatiuk, Viktoriya (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2024)
The purpose of the scientific paper is a philosophical and legal comprehension of the concept of "human". Research methods: to achieve a specific goal, philosophical, general scientific, and special-legal methods were used, in particular, the dialectical, historical, structural-functional, comparative, logical-legal, and the like. Results: the issue of uncertainty of the concept of "human" is resolved at the interdisciplinary level, including within the framework of philosophical and legal science. Philosophical and legal research on the definition of the concept of "human" will contribute to the achievement of theoretical-scientific and social-practical goals, in particular, it will help to avoid existing disagreements, to resolve numerous problematic issues that are a priority at the current stage of development of jurisprudence and related to human rights. Discussion: the philosophical and legal analysis of the concept of "human" is aimed at considering it in harmony with the biological, social, and spiritual essence of human. The issues of unification of this concept in various legal systems remain controversial in this context due to the diversity of cultural and religious beliefs, the lack of regulation of the issue of biotechnology, artificial intelligence, fetal rights, and decisions on the end of life. It is important that with the change in society, and the emergence of new technologies, the definition of what it means to be human also changes. All this requires constant legal, ethical, and philosophical discussions to adapt laws to new challenges while ensuring the observance of fundamental human rights.